Age-related changes in creative thinking during late childhood: The contribution of cooperative learning - Segundo Marcos, Rafael Ibán; Merchan Carrillo, Ana; López-Fernández, Verónica; Daza-González, María Teresa (Thinking Skills and Creativity, 2023)
Creative thinking has been considered a human skill that is necessary for facing challenging situations that require adaptive solutions. From an educational perspective, creative thinking plays an important role in learning processes and is an issue of central importance within classroom methodology. In this regard, Cooperative learning (CL) has been studied as a methodology that enhances creative processes. CL methodology refers to teaching procedures based on organizing the class into small mixed-abilities groups where students work cooperatively to complete academic tasks and consolidate their learning. However, the impact of CL on creative thinking seems to have been insufficiently explored in late childhood, which is known as a transitory stage between childhood and adolescence. Using two tests (at 5th and 6th grades of Primary School), we examined the trajectory of creative thinking in fifty-three students from two different schools. Students were assessed by a divergent thinking task (CREA Test; Corbalán et al., 2015) at two time points: Test-1 (T1), with a mean age of 9.81 years (Sd= 0.48), and Test-2 (T2), with a mean age of 11.35 years (Sd= 0.52). Given the differences in methodology delivered in each school (Cooperative and individualistic learning), we also analyzed the effects of this variable on student creative thinking performance. We found significant improvements between testing in the two schools, although CL appeared to have a more positive effect than IL on creative thinking performance. Our finding highlights the importance of studying classroom methodology as a mediating factor in creative thinking development, which could be important in the learning processes as well as the integral development of the child.
Keywords: classroom methodology; cooperative learning; creative thinking; divergent thinking test; Scopus; JCR